HepCare Europe—A service innovation project. HepCheck: Characteristics of the patient population with active infection as defined by HCV RNA. (February 2020) - Avramovic, Gordana; Oprea, Cristiana; Surey, Julian; Story, Alistair; Macías, Juan; Cullen, Walter; Iglesias, Maria; Mc Hugh, Tina; Crowley, Des; Naughton, Anna Marie; Horan, Aidan; Ianache, Irina; et al.
Highlights: The main risk factors for hepatitis C virus (HCV) infection are injecting drug use and homelessness. Many vulnerable patients remain undiagnosed or 'lost to follow-up'. Variances in rates of new and previously known diagnoses exist between countries. These variances highlight the need for different strategies of HCV care. Abstract: Background: Hepatitis C virus (HCV) is a main cause of chronic liver disease worldwide and is consistently under-diagnosed. Community-based screening initiatives, such as HepCheck, have been identified as important components of HCV care. HepCheck focuses on screening and identifying HCV RNA-positive cases in high-risk populations and linking them to care as part of a larger European project to improve HCV care (HepCare). Methods: HCV testing with a self-administered questionnaire was offered to 2822 individuals. Results: There were 2079 patients screened. Overall, 397 (19%) of the total screened cohort were identified as having active HCV infections as measured by HCV RNA PCR. The patients were mostly male (84%), white (88%), and had a history of injecting drug use (IDU) (86%), homelessness (58%), and tattooing (42%). There were 136 new cases (7% of the total sample and 34% of identified active infections). Romania had the highest proportion of newly identified cases with 87%, then Ireland with 60%, and Spain with 43%; the UK had the lowest proportion of new cases at 10%. Conclusions: For those lost to follow-up, a major strategy is re-engagement. For those newly diagnosed, the 'seek and treat' approach is a key strategy. Thus, different priorities are defined for different countries.